Analisis Kasus Korupsi Proyek Pembangunan Jalan Lingkar Kota Slawi (Jalingkos) di Kabupaten Tegal - Ica Paramastri; Budi Setiyono; Rina Martini (Journal of Politic and Government Studies, 2013)
One of the most crucial issues to be solved by the government of Indonesia is the problem of corruption. This is because the longer the corruption in Indonesia increasingly difficult to overcome. This is because corruption carried out in a systematic and organized from the bottom level to the level of officials. As happened in Tegal regency, corruption fund development projects Slawi city ring road, known as Jalingkos made by former Tegal Regent Agus Riyanto, Edy Prayitno, and Budi Haryono worth 3.4 Billion. Corruption is a neat eventually be leaked by a number of activists who are members of NGOs GMTB (tegal Unite People movement). . The results showed that the Agus Riyanto, Edy Prayitno, and Budi Haryono has proven corrupt jalingkos project development funds for their personal interests respectively. Law enforcement on the case jalingkos assessed later and said selective loggingAgus Riyanto was sentenced 5 years 6 months in jail, pay a fine of USD 200 million with a substitute punishment for one year in jail and pay compensation amounting to Rp 1.4 billion, or imprisonment for three years, Edy Prayitno was sentenced 5 years 6 months in prison and a fine of Rp 200 million and reimbursement of compensation amounting to Rp 1,494,410,000, Budi Haryono sentenced to 4 years in prison plus a fine of Rp 200 million and cash compensation of Rp 747,205,000.Keywords: Analysis of case, Corruption, Development Project Slawi Town Ring Road (Jalingkos).